(untitled) (Annals of Medical Research, 2021)
Aim: Tacrolimus is an immunosuppressive agent used for prophylaxis of organ rejection after solid organ transplantations. Neuropsychiatric adverse effects that occur in the first 4 weeks following initiation of tacrolimus defined as early tacrolimus-induced neurotoxicity (TIN). In our study, we aimed to determine the incidence of possible TIN and to examine its association with tacrolimus blood levels and establish other medical and clinical factors to predict in patients with liver transplantation.Material and Methods: This retrospective, single-center study was conducted at a transplantation unit of tertiary level university hospital. All the patients were enrolled, who undergone liver transplantation between January 2013 and December 2018. Tacrolimus blood levels were obtained the day after the initiation of tacrolimus and for consecutive 10 days. All the patients z-scores calculated for tacrolimus mean blood levels until index day. Index day is defined as ‘the day of diagnosis of possible TIN’. Age, gender, previous encephalopathy, cadaveric/live donor transplantation, pre-transplantation MELD score, CRP levels and tacrolimus blood levels were investigated as predictors of possible neuropsychiatric events following liver transplantation in two weeks.Results: Tacrolimus z-scores were detected to be significantly different between groups; found to be lower in the possible tacrolimus-induced neurotoxicity group compared to the control group (t=2.607, p=0.01). Pre-transplantation model significantly predicts neuropsychiatric adverse events(χ²(7)=16.049, p=0.035). Conclusion: To our knowledge, this is the first study that shows an inverse association with tacrolimus blood levels and possible TIN; which requires consideration. It is obvious that further well designed, prospective studies are needed to clearly establish risk factors for TIN.